THE CORRELATION OF ABO BLOOD TYPES AND COVID-19 SEVERITY IN BETHESDA HOSPITAL YOGYAKARTA - Pranata, Korin Bagas; Probowati, Wiwiek; Wuryaningsih, Nining Sri (Faculty of Medicine Universitas Kristen Duta Wacana, 2023)
Background COVID-19 is caused by the SARS-CoV-2 virus. The most recent study showed that there was a possible correlation between ABO blood types and COVID-19 risk. However, some studies disproved the correlation. The contradiction indicated that the correlation between the two variables has not been established. Objective To find the correlation between ABO blood types and the severity of COVID-19. Methods It applied an observational-analytic method with a retrospective cohort approach. It used secondary data from 2020-2021 in Bethesda Hospital Yogyakarta. Samples were taken using a consecutive sampling technique. The collected data were analyzed using SPSS 26. Univariate analysis was made using descriptive statistics. Sequentially, bivariate and multivariate analyses were made using chi-square, odds-ratio, relative-risk, and ordinal logistic regression analysis. Results There were 212 data. Blood type O got the biggest percentage (38.2%) with a sample of 81 individuals. There were 88 patients with severe symptoms (41.5%), 86 patients with moderate symptoms (40.6%), and 38 patients with mild symptoms (17.9%). The Chi-square analysis of ABO blood types and the severity of COVID-19 was 0.05 (?0.05). The blood type B had a 2.8 times higher probability of severe incidence (95% CI 0.618–12.16) than the non-B blood type. Meanwhile, blood type O had a 0.33 times lower probability of severe incidence (95% CI 0.618–12.16) than non-O blood type. Conclusion The ABO blood types correlated with COVID-19 severity. Blood type O became a protective factor, and blood type B is the risk factor for severe COVID-19. TRANSLATE with x English Arabic Hebrew Polish Bulgarian Hindi Portuguese Catalan Hmong Daw Romanian Chinese Simplified Hungarian Russian Chinese Traditional Indonesian Slovak Czech Italian Slovenian Danish Japanese Spanish Dutch Klingon Swedish English Korean Thai Estonian Latvian Turkish Finnish Lithuanian Ukrainian French Malay Urdu German Maltese Vietnamese Greek Norwegian Welsh Haitian Creole Persian Â Â TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster Portal Back